Perspektif Pendidikan dan Keguruan, Vol VI, No. 12, Oktober 2015 ISSN 1411-3570 63 PENGEMBANGAN LEMBAR KERJA SISWA (LKS) POKOK BAHASAAN STOIKIOMETRI BERBASIS PBL UNTUK MENINGKATKAN KEMAMPUAN METAKOGNITIF SISWA: (Development of Student Work Sheet (LKS) Stoichiometry Based on PBL to Improve Students’ Metacognitive Skills) - Radjawaly Usman Rery (Perspektif Pendidikan dan Keguruan, 2015)
The aims of this research is to Develope the student worksheet (LKS)-based on problem based learning to advance student metacognitive in stoichiometric topic. The method of this Researh and Develompment (R & D) used 4-D model, the research instruments that was developedused Likert scale. The resulte of thisresearch such a form student worksheets of laboratory based on problem based learning in stoichiometric topic. Validation obtained that the worksheets developed for the requirements of the material was given a score of 3.2 ( good ), requirements language have score 3.4 ( very good ) and construction requirement score 3.2 ( good ). Results of testing the student 's response indicates that, the worksheet in a good category. This worksheet developed student metacognitive. Worksheet were developed feasible to use to develop metacognitive skills of students on the subject of stoichiometric.